Beiträge zur deutschen und slowenischen Phraseologie und Parömiologie - Jesenšek, Vida (University of Maribor Press, 2021)
Contributions to German and Slovenian Phraseology and Paremiology.The monograph consists of three parts. Twelve contributions presented on several aspects of German and Slovenian phraseology represent a selection of authors phraseological studies, mostly related to the language contrastive (German-Slovene) research topic. Part I deals with typical aspects of proverbs from the perspective of system-related research. This is followed by contributions on the lexicographical and translational problems of phraseology (Part II). The volume ends with reflections on appropriate treatment of phraseology in the learning and teaching contexts (Part III). German as the primary language of observation plays an important role in all the contributions because its status as an influential language in Slovenia is increasingly challenged. It is worth mentioning that in the past, German used to exert much greater historical, cultural, and linguistic influence on the Slovenian society. By combining different research perspectives and linguistic contrastive approaches, the volume intends to appeal to linguists as well as practising translators and language teachers.